2013
DOI: 10.3111/13696998.2013.802241
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal analysis of costs associated with change in disease activity in systemic lupus erythematosus

Abstract: Only short-term effects of disease activity change were investigated, disregarding other potential benefits of low disease activity on long-term organ damage prevention or comorbidities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(39 citation statements)
references
References 10 publications
1
38
0
Order By: Relevance
“…44,45 The total all-cause healthcare costs substantially increased by 71% during the post-index date period (US$26,998) compared with the pre-index date period (US$15,746). Kan et al 37 estimated an average of US$18,839 annual healthcare costs in patients with SLE, while other studies reported costs up to 3-fold higher among patients with SLE, 41,46 depending on SLE severity and payer type. Lowest costs were observed among patients with mild SLE covered by commercial insurers, while highest costs were observed among patients with moderate or severe SLE covered by Medicaid.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…44,45 The total all-cause healthcare costs substantially increased by 71% during the post-index date period (US$26,998) compared with the pre-index date period (US$15,746). Kan et al 37 estimated an average of US$18,839 annual healthcare costs in patients with SLE, while other studies reported costs up to 3-fold higher among patients with SLE, 41,46 depending on SLE severity and payer type. Lowest costs were observed among patients with mild SLE covered by commercial insurers, while highest costs were observed among patients with moderate or severe SLE covered by Medicaid.…”
Section: Discussionmentioning
confidence: 99%
“…SLE disease severity (mild, moderate, and severe) and proportion of patients with flares by severity (mild, moderate, and severe) in the pre-and post-index date periods were identified using published algorithms. [36][37][38] HCRU outcomes encompassed inpatient admissions, emergency department (ED) visits, physician office visits, outpatient/other ancillary visits, and medication use, and were assessed during the pre-and post-index date periods. A list of the medications considered to be SLE-related is available in Supplementary material (Supplementary Table ).…”
Section: Variables and Outcome Measuresmentioning
confidence: 99%
“…However, higher costs have been reported for patients with LN [14,16], with a mean annual direct cost range of US$29,034-$62,651 [14]. Increased disease activity and organ damage have also been shown to increase costs in patients with SLE [17][18][19][20]. Despite this, few studies have evaluated the economic burden of the subgroup of patients with LN.…”
Section: Introductionmentioning
confidence: 99%
“…Analyses were also conducted to examine the relation of clinician-recorded SLEDAI scores and eSLEDAI score categories to healthcare resource utilisation, pain medication prescriptions and corticosteroid prescriptions, as previous studies have shown that resource utilisation including medication usage increases with increased disease activity. 11 12 While a comparison of the eSLEDAI score category to a clinician-recorded SLEDAI score cannot be done for these SLE Registry encounters, the performance of the model can still be assessed based on other types of medical data. In these analyses, we compared trends in healthcare resource utilisation, pain medication prescriptions and corticosteroid prescriptions across the four estimated SLEDAI categories to trends across clinician-recorded SLEDAI scores as independent measures of the model’s performance in a real-world dataset.…”
Section: Methodsmentioning
confidence: 99%